Exploring Semantic Component and Expansion: Unpacking the Layers of Meaning in â€œKung Tuyo Na Ang Luha Mo, Aking Bayanâ€ by Amado V. Hernandez - Mar Fernandez Martin; Cristian Gregor E Atacador (Prominent, 2025)
This study explores the semantic components and expansions of â€œKung Tuyo na ang Luha Mo, Aking Bayan,â€ focusing on the linguistic experiences of the author in the poem, semantic components, semantic expansion, and implications in education. Relational qualitative content analysis was utilized to unpack the poem systematically. The findings highlight significant semantic components and expansion in line/s such as â€œLumuha ka, aking bayan; buong lungkot mo iluhaâ€, Personification, depicted as a person crying, symbolizing national grief under colonial oppression, additionally, â€œKatulad mo ay si Huli, naaliping bayad-utang, katulad mo ay si Sisa, binaliw ng kahirapanâ€, Simile, the nation is compared to Rizalâ€™s tragic characters Juli and Sisa, symbolizing suffering under colonial and systemic oppression. Moreover, with words/phrases like "Lukob ng dayong bandila" or "Covered by a foreign flag", the Philippines is metaphorically overshadowed by foreign domination, symbolizing lost sovereignty. "Sisigaw kang buong giting sa liyab ng libong sulo" or "You will shout courageously in the blaze of a thousand torches.", The phrase signifies unity and revolution, portraying a collective uprising. Therefore, students significantly appreciate literature and how helpful it is in fostering historical and national knowledge as identity. This research provides a foundation to include works like "Kung Tuyo Na ang Luha Mo, Aking Bayan" in the curriculum, encouraging students to interact with texts to drive social change and cultivate a greater appreciation for Philippine literature.